2017
DOI: 10.1002/oby.21938
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Enhances the Effects of Alpha‐Linolenic Acid Against Visceral Fat: A Double‐Blind Randomized Controlled Trial

Abstract: ObjectiveTo investigate the effect of alpha‐linolenic acid‐rich diacylglycerol (ALA‐DAG) compared with alpha‐linolenic acid‐rich triacylglycerol (ALA‐TAG) on visceral fat area (VFA) in people with overweight.MethodsSubjects with overweight were recruited to a randomized, double‐blind, controlled, parallel‐group designed trial and randomly allocated to two groups that consumed either 2.5 g/d ALA‐TAG or ALA‐DAG for 12 weeks. Two 4‐week nontreatment periods were placed before and after the treatment period. One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…A 12‐week trial showed that after 14 obese patients underwent ALA treatment (4.0 g/day), the expression of PPAR‐γ and G0/G1 switch gene 2 in peripheral blood mononuclear cells increased, and the plasma FFA levels decreased (Zhao, Wang, & Guo, 2016). A 12‐week trial showed that ALA‐rich diacylglycerol (2.5 g/day) could reduce the visceral fat area, body mass index, and serum triacylglycerol content in 57 overweight subjects (Saito, Mori, Osaki, & Katsuragi, 2017). (d) Effects on metabolic syndrome subjects.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…A 12‐week trial showed that after 14 obese patients underwent ALA treatment (4.0 g/day), the expression of PPAR‐γ and G0/G1 switch gene 2 in peripheral blood mononuclear cells increased, and the plasma FFA levels decreased (Zhao, Wang, & Guo, 2016). A 12‐week trial showed that ALA‐rich diacylglycerol (2.5 g/day) could reduce the visceral fat area, body mass index, and serum triacylglycerol content in 57 overweight subjects (Saito, Mori, Osaki, & Katsuragi, 2017). (d) Effects on metabolic syndrome subjects.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…2325 Clustering of metabolic risk factors, such as hypertension, high blood glucose and triglyceride concentrations, and low serum high-density lipoprotein cholesterol, is more strongly associated with VFA than high subcutaneous fat, WC, or BMI. 2628 Reducing VFA could decrease the risk of metabolic syndrome-related disease. Thus, the association between the gut microbiota and VFA might be more important clinically than the association between the gut microbiota and BMI, especially with regard to metabolic syndrome-related disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Li et al investigated the beneficial effects of DAG consumption on T2D patients, demonstrating an improvement not only in relation to body weight and waist circumference, but also regarding glucose metabolism and blood pressure compared with TAG [206]. Pointing in the same direction, the consumption of DAG together with alpha linoleic acid (ALA), a fatty acid undergoing easier beta oxidation as opposed to palmitic, stearic, oleic, or linoleic acid [207][208][209], resulted in excellent outcomes on body weight and visceral fat loss [203,210,211].…”
Section: Diacylglycerolmentioning
confidence: 99%